Impact of Lined Canal on Shallow Tubewell Irrigation and Their Acceptability by the Farmers - Sayed, Abu; Saleh, A F M; Hossain, Md. Altaf; Basunia, Zobayer Ali; Hosain, Md. Afzal (The Agriculturists, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The comparative conveyance losses between lined and unlined canals, impact of water saving on command area development and irrigation cost, and farmers acceptability of lined canal in shallow tubewell (STW) irrigation schemes were studied during 2010-11 Boro season at three upazilas: Manikgonj Sadar of Manikgonj district, Dhamrai of Dhaka district and Mithapukur of Rangpur district. The conveyance loss was measured using inflow-outflow method and focus group discussion (FGD) was carried out with the pump owners and farmers to assess the impact of water saving on command area development and the acceptability of lined canal technology. Average conveyance losses were found to be 41, 48 and 45% in the existing earthen canals; 18, 21 and 24% in improved earthen canals; and 12, 11 and 13% in pre-cast canals at Mithapukur (M1), Manikgonj Sadar (M2) and Dhamrai (D) schemes, respectively. The water saving did not increase the command area in any of the schemes but reduced the irrigation time and saved fuel requirement for irrigation. On an average, 32, 23 and 30% fuel were saved by improved earthen canals where as 45, 46 and 48% were saved by pre-cast canals for M1, M2 and D schemes compared to earthen canal. The benefit-cost ratios of improved earthen canals were 1.36, 1.38 and 1.30 where as 3.36, 4.28 and 3.34 by pre-cast canals for M1, M2 and D schemes, respectively. The internal rate of return (IRR) from the investment on water distribution was over 50%. The lining technology was acceptable to pump owners, but did not impress the farmers who share the crop with the pump owners as price of irrigation or pay on the basis of irrigated area. In order to make the technology acceptable to the farmers, polices must be framed to share the benefits of lining by the pump owners with the farmers by reducing the price of irrigation water or through financial support of GO and NGOs for efficient use of STW irrigation system in Bangladesh. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) 116-125 <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->